PERANCANGAN APLIKASI KOPERASI SYARIAH SIMPAN PINJAM BERBASIS WEB (STUDI KASUS KOPERASI BMT DARUL MUTTAQIEN) - Auzan Muhammad Yustanto; Sri Mulyati (CV. Multi Kreasi Media, 2023)
Abstract− Baitul Maal Tamwil (BMT) is an institution consisting of two terms, namely baitul maal and baitul tamwil. This institution was established with the intention of facilitating the lower communities that are not reached by the services of Islamic banks or Islamic BPRs. The operational principles used are the principles of profit sharing, buying and selling and entrustment. Therefore, although it is similar to the Islamic bank BMT has its own market, namely a small community. It's just that what distinguishes sharia cooperatives from other cooperatives is the operational system. The sharia system in sharia cooperatives does not allow usury or in its default language it is called